2021
DOI: 10.1186/s12889-021-12116-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal movement behaviors: correlates and associations with anxiety symptoms among Chinese university students

Abstract: Background The Canadian 24-Hour Movement Guidelines for Adults was released in 2020. There is a dearth of evidence on the association between adherence to the 24 h movement guidelines and health indicators. This study aims to (a) explore the associations between potential correlates and meeting the 24 h movement guidelines using a sample of Chinese university students; and (b) examine if meeting 24 h movement guidelines is associated with the severity of anxiety symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Few published studies have evaluated adherence to the overall 24-hour movement guidelines among university students (60)(61)(62)(63). Consistent with our findings, two studies reported similar rates of meeting recommendations among Canadian university students-9.9% and 8.4% (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Few published studies have evaluated adherence to the overall 24-hour movement guidelines among university students (60)(61)(62)(63). Consistent with our findings, two studies reported similar rates of meeting recommendations among Canadian university students-9.9% and 8.4% (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined associations of meeting 24-HMB guidelines with some aspects of internationalizing and/or externalizing problems among different age groups (e.g., preschoolers, youths, and emerging college students) with healthy or clinical condition ( Bu et al., 2021 ; Hou et al., 2023 ; Ohta et al., 2023 ; Patte et al., 2020 ; Sampasa-Kanyinga et al., 2021 ; Zhu et al., 2023 ). For instance, a cross-sectional study indicated that meeting all three components of 24-HMB guidelines was linked to fewer internalizing and externalizing problems among preschoolers aged 3–6 years ( Zhu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A healthy lifestyle may be a key determinant in preventing Internet addiction (IA) [ 10 12 ]. Research indicates that healthy lifestyle behaviors, including nutritious eating, contribute significantly to mental health.…”
Section: Introductionmentioning
confidence: 99%